The codicil : a novel - Topor, Tom (New York : Hyperion, 1995)
After a millionaire dies, his wife and children learn that half his fortune will go to a child he fathered during the Vietnam War, provided the child is still alive. Lawyer Adam Bruno sets out to find the boy before some members of the family do.
National College of Business and Arts
Keywords: Inheritance and succession -- Fiction; Detective and mystery fiction